Temperature impact of nitrogen transformation in technological system: vertical flow constructed wetland and polishing pond = Wpływ temperatury na przemiany azotu w układzie technologicznym: złoże hydrofitowe o przepływie pionowym i staw doczyszczający - Myszograj, Sylwia; Bydałek, Franciszek (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article describes the results of the research, purpose of which was to evaluate influence of the temperature on the effectiveness of nitrification and denitrification in the sewage treatment system consisting of vertical flow constructed wetland and polishing pond. During the analysed period, the efficiency of removing total nitrogen was low and amounted to 12.7%.
Keywords: constructed wetlands; temperature; nitrogen removal; first-order kinetics; oczyszczalnie hydrofitowe; temperatura; usuwanie azotu; kinetyka pierwszego rzędu